Ecofisiologia, rendimento e qualidade de morangueiro de dias neutros cv. albion em diferentes substratos - Costa, Rosiani Castoldi da (2012)
The growth system in substrate allows to increase the yield per area and to improve the fruits quality, using different material for the development of the plants. Allied to these factors, there is the possibility of producing off season fruits through genotypes which are indifferent to photoperiod, anticipating or extending the cycle of the crop, using (storaged) and/or fresh vernalized seedings. Given the above considerations, the objective of this work is to evaluate the physiological and agronomic performance of cultivar Albion (neutral days) led in different substrates in protected ambient. The research was accomplished in the Agronomy College of Passo Fundo University from August 2009 to April 2011. The work was divided into three experiments. In the first one, the leaf water potential and gas exchange of the plants achieved in different substrates was determined. In the second one, phenology, phyllochron and leaf area were evaluated and, in the third one, the development of cv. Albion as for fruit production and quality during the harvest period was determined. The seedings were transplanted in containers (plastic bags) placed on benches, filled with different substrates, which consisted of treatments and were formed by five different portions of two materials (Carbonized rice husk and commercial substrate Mec Plant Horta 2®). The experimental design was consisted of randomized complete blocks with four repetitions and eight plants per plot. The results were submitted to the analysis of variance and the differences compared by the Tukey test at 5% of error probability and regression analysis. The results related to ecophysiology showed that the lowest water potential recorded in the strawberry leaves cv. Albion was -1.56 MPa in substrate with 75% CAC+25% Horta 2® in room temperature of 40°C. At the 425 DAT, the stomatal conductance is inferior to 0.05 mol H2O m-2 s-1, reducing the strawberry photosynthetic rate. The vernalizing process anticipates the cycle of strawberry cv. Albion. The leaves length and width are adequate to the leaf area estimate. The different substrate combinations do not interfere in the production and in the physic-chemical parameters analyzed. Therefore, there is influence of harvest periods. It is possible to extend the production until February and April, setting up production in the offseason. Maximum production is obtained in January 2011 (526 g) and December 2010 (465 g). Fruits are harvested in January 2010 and April 2011, and their total sugar/acidity is higher in April (15.31) 2011.